Social Influence and Elderly Smartwatch Adoption: A Case Study - Irina CRISTESCU; Dragoș-Daniel IORDACHE; Eugenia TÎRZIU; Eleonora TUDORA; Maria GHEORGHE-MOISII (Communications of International Proceedings, 2022)
Social influence (SI) is an important factor in adopting wearable technology. In the context of a fast-aging population smartwatches (SWs) have the advantage of responding to specific healthcare and assistance needs, which comes as an advantage when dealing with the older population. This study investigates the role of SI in elderly’s acceptance of   smartwatches. The proposed model is based on the TAM model. The results showed that SI has an indirect effect on the behavioral intention (BI) to adopt SWs, while perceived ease of use (PEOU) and perceived utility (PU) are stronger determinants of the behavioral intention (BI).
Keywords: smartwatch; smartwatch adoption; technology acceptance model; social influence